Sprachenvielfalt und regionale Differenzierung von Glaubensgemeinschaften im Hindukusch-Karakorum.: Zur Rolle von Minderheiten im Konfliktfeld Nordpakistans - Kreutzmann, Hermann (ERDKUNDE, 1995)
Ethnic conflicts and restricted socio-economic participation of minority groups have attracted increased attention in post-colonial societies of heterogeneous population composition. Regionalism, communalism and ethno-linguistic differentiation are catchphrases related to social developments in the Indo-Pakistan subcontinent. The role of mountain societies that are deprived of substantial civil rights has been neglected in this context. Comparatively small populations inhabit the Hindukush- Himalayan mountain arc. Within high mountain research these areas have been termed regions of refuge, characterized by isolation, remoteness and limited to non-existent exchange relations. This study follows a different approach based on a historical reconstruction of population processes. Ethnoterritoriality of marginal groups seems to be the result of participation in superordinate development processes and of the simultaneous persistence of ethno-linguistic features. Empirical evidence is presented from recent fieldwork in the Eastern Hindukush and Karakoram. The analysis of demographic, linguistic and denominational parameters has supported the thesis of the exceptional position of high mountain habitats. The study area significantly differs in these parameters from lowland Pakistan. On the other hand, conflict situations like communalistic or sectarian clashes follow similar lines all over the country. The formation of social groups and the inclusion of different features relate to the level of hierarchy and are not necessarily based on essential traits. Group confrontation and group identity have to be analyzed in the context of conflict constellations. The existence of isolated linguistic domains superficially suggests conservation through remoteness. Nevertheless, lowland-highland migration and intra-montane mobility seem to be the driving force of population differentiation. These forces support an enhanced linguistic and denominational diversification. I creased accessibility, growing mobility and improved exchange relations has not so far reduced the persistence of these factors.